Online Typhoon Preparedness and Mitigation Program: Fitness-for-Purpose Process - Villarino, Resti Tito (Technium Social Sciences Journal, 2023)
Awareness, education, preparedness, predictive, and early warning systems can assist communities in mitigating the disruptive consequences of natural disasters like typhoons. Preparation for and mitigation of typhoons are vital to disaster risk management because they provide accurate and pertinent knowledge, skills, and attitude before, during, and after typhoon processes. This article summarizes an innovative, evidence-based strategy for creating an online typhoon preparedness and mitigation program anchored on Macroergonomics, Typhoon Adaptation, Typhoon Awareness, Risk Perception, and Perceived Preparedness. Moreover, the program was developed from the adapted and contextualized Community Disaster Preparedness Handbook, Weather Underground, the Tropical Cyclone and Typhoon Action, and the Philippines' National Risk Reduction and Management Plan. It examines potential future directions for analyzing, evaluating, and documenting the fitness-for-purpose procedure.